2015
DOI: 10.1371/journal.pone.0120281
|View full text |Cite
|
Sign up to set email alerts
|

Functional Integration of Human Neural Precursor Cells in Mouse Cortex

Abstract: This study investigates the electrophysiological properties and functional integration of different phenotypes of transplanted human neural precursor cells (hNPCs) in immunodeficient NSG mice. Postnatal day 2 mice received unilateral injections of 100,000 GFP+ hNPCs into the right parietal cortex. Eight weeks after transplantation, 1.21% of transplanted hNPCs survived. In these hNPCs, parvalbumin (PV)-, calretinin (CR)-, somatostatin (SS)-positive inhibitory interneurons and excitatory pyramidal neurons were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…On the other hand, the physiological environment of organotypic tissue cultures might be compromised by a lack of blood flow and morphological modifications with increasing time of tissue maintenance. It remains unclear whether conditions in vivo accelerate the maturation of neural precursor cells since the functional properties of differentiated neurons (firing pattern or network activity) are typically studied a few months following their transplantation into the brain (Zhou et al, 2015;Avaliani et al, 2014;Tornero et al, 2017;Oki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the physiological environment of organotypic tissue cultures might be compromised by a lack of blood flow and morphological modifications with increasing time of tissue maintenance. It remains unclear whether conditions in vivo accelerate the maturation of neural precursor cells since the functional properties of differentiated neurons (firing pattern or network activity) are typically studied a few months following their transplantation into the brain (Zhou et al, 2015;Avaliani et al, 2014;Tornero et al, 2017;Oki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1 D , E ; Alvarez-Dolado et al, 2006; Hunt et al, 2013; Howard et al, 2014; Sebe et al, 2014b; Zhou et al, 2015), it is not yet settled whether they also have proper synaptic characteristics matching their interneuron subtypes. Comprehensive recapitulation of functional features is essential to any type of cell-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Organoids are three-dimensional systems in which iPSCs partially regulate their own differentiation into a specific tissue type, resulting in a model tissue that closely recapitulates the normal process of development. The majority of brain organoid protocols generate tissues with gene expression patterns most similar to the second trimester of in utero development or younger [91][92][93][94]. Recent technical improvements in organoid technology and prolonged periods in culture may enable scientists to model later stages of fetal development [95].…”
Section: Organoidsmentioning
confidence: 99%
“…Although many human neuronal culture systems are limited in their ability to generate mature neurons with normal electrophysiological properties, xenograft systems have not only met with success in this area, but they have also shown that many of the signaling cues for development and migration of neurons are common between mice and humans. Multiple groups have shown that human iPSC-derived cells introduced into the mouse brain migrate to their proper location and develop mature characteristics of their specified cell type [91,106,107]. Although xenograft systems do not mimic a fully human context, they are uniquely well suited for studies of how iPSC-derived neurons integrate into a functional neuronal circuit in a brain, which no current iPSC-only model can (yet) do.…”
Section: Xenograft Studiesmentioning
confidence: 99%